If it's not what You are looking for type in the equation solver your own equation and let us solve it.
27x-9=x
We move all terms to the left:
27x-9-(x)=0
We add all the numbers together, and all the variables
26x-9=0
We move all terms containing x to the left, all other terms to the right
26x=9
x=9/26
x=9/26
| -4y+5=27-19 | | 9/(2x-1)=3/6 | | 8^2x=2^x+5 | | 6x+40=14x-8 | | 18+5d=83 | | 0=+n | | 2x+179=10x-5 | | x+.45x=100 | | 6(c+4)=84 | | 3a+6-2a=1 | | .05(x-8)+.25x=4.1 | | 2x^2+2x-336=0 | | -8(x+6)=2(x-64( | | 13x+2+5x+24+7x+7+8x-3=360 | | -4x-5=29 | | (x-10)x5=15 | | 1.4x=21 | | 1/4((2k+1)*(2k+1)+3)=2k+1 | | u/4+11=14 | | 1/2x−5+2/3x=7/6x+4 | | 5g-7+2g=3+2g | | 26=y+18 | | 8x-26÷6=x-3 | | 3z/7+4/1=-3 | | 4(p-7)=-28 | | 75=x-12 | | 3x-8=61-5x+4=1 | | 5(x-3)+3=6x+15 | | x+x-40=68 | | 2p+10=12 | | 3x-8=61-5x | | 2x+1=4,x+1= |